Absence of ERRalpha in female mice confers resistance to bone loss induced by age or estrogen-deficiency. - Catherine Teyssier; Marlène Gallet; Bénédicte Rabier; Laurent Monfoulet; Julien Dine; Claire Macari; Julie Espallergues; Béatrice Horard; Vincent Giguère; Martine Cohen-Solal; Olivier Chassande; Jean-Marc Vanacker (PLoS ONE, 2009)
BACKGROUND:ERRalpha is an orphan member of the nuclear hormone receptor superfamily, which acts as a transcription factor and is involved in various metabolic processes. ERRalpha is also highly expressed in ossification zones during mouse development as well as in human bones and cell lines. Previous data have shown that this receptor up-modulates the expression of osteopontin, which acts as an inhibitor of bone mineralization and whose absence results in resistance to ovariectomy-induced bone loss. Altogether this suggests that ERRalpha may negatively regulate bone mass and could impact on bone fragility that occurs in the absence of estrogens. METHODS/PRINCIPAL FINDINGS:In this report, we have determined the in vivo effect of ERRalpha on bone, using knock-out mice. Relative to wild type animals, female ERRalphaKO bones do not age and are resistant to bone loss induced by estrogen-withdrawal. Strikingly male ERRalphaKO mice are indistinguishable from their wild type counterparts, both at the unchallenged or gonadectomized state. Using primary cell cultures originating from ERRalphaKO bone marrow, we also show that ERRalpha acts as an inhibitor of osteoblast differentiation. CONCLUSION/SIGNIFICANCE:Down-regulating ERRalpha could thus be beneficial against osteoporosis.